Design, synthesis, and cytotoxic activities of novel hybrids of parthenolide and thiazolidinedione via click chemistry. Issue 5 (3rd May 2020) - Qiu, Jie; Yuan, Chun-Mao; Wen, Min; Li, Ya-Nan; Chen, Juan; Jian, Jun-You; Huang, Lie-Jun; Gu, Wei; Li, Yan-Mei; Hao, Xiao-Jiang
Abstract: A series of novel parthenolide–thiazolidinedione hybrids have been synthesized via a click chemistry-mediated coupling between parthenolide and thiazolidinedione, and evaluated for their cytotoxic activities. The results indicated that all the hybrids showed moderate cytotoxic effects on human cancer cell lines, including human erythroleukemia cell line (HEL), prostate (PC3), and breast (MDA-MB-231) by MTT assay. In particular, compound VI-6 exhibited the best cytotoxic activities against the MDA-MB-231 cells with IC50 value of 2.07 µM, which was about eight times more active than that of the original compound (PTL ). These interesting results might be used to develop novel lead scaffolds for potential anticancer agents. Graphical Abstract: